The lethal(2)-essential-for-life [L(2)EFL] gene family modulates dengue virus infection in aedes aegypti - Lucky R. Runtuwene (2020)
© 2020 by the authors. Licensee MDPI, Basel, Switzerland. Efforts to determine the mosquito genes that affect dengue virus replication have identified a number of candidates that positively or negatively modify amplification in the invertebrate host. We used deep sequencing to compare the differential transcript abundances in Aedes aegypti 14 days post dengue infection to those of uninfected Ae. aegypti. The gene lethal(2)essential-for-life [l(2)efl], which encodes a member of the heat shock 20 protein (HSP20) family, was upregulated following dengue virus type 2 (DENV-2) infection in vivo. The transcripts of this gene did not exhibit differential accumulation in mosquitoes exposed to insecticides or pollutants. The induction and overexpression of l(2)efl gene products using poly(I:C) resulted in decreased DENV2 replication in the cell line. In contrast, the RNAi-mediated suppression of l(2)efl gene products resulted in enhanced DENV-2 replication, but this enhancement occurred only if multiple l(2)efl genes were suppressed. l(2)efl homologs induce the phosphorylation of eukaryotic initiation factor 2α (eIF2α) in the fruit fly Drosophila melanogaster, and we confirmed this finding in the cell line. However, the mechanism by which l(2)efl phosphorylates eIF2α remains unclear. We conclude that l(2)efl encodes a potential anti-dengue protein in the vector mosquito.